Europe as an agent of change: The role of the European Court of Human Rights in Turkey's Kurdish policies - Dilek Kurban (Stiftung Wissenschaft und Politik (SWP), 2014)
Notwithstanding the ongoing negotiations between the PKK and the government, the crux of Turkey's Kurdish issue remains the structural inequalities against the Kurds, which are deeply rooted in an anti-democratic politico-legal regime. Certainly, Turkey has come a long way in acknowledging the Kurdish issue and taking steps to address the Kurds' demands for equality and the rule of law. Once banned from speaking their language, Kurds can now use it to attain a university education. The Kurdish region is no longer governed by a state of emergency, nor are Kurdish civilians disappearing under detention. There is no doubt that the European Court of Human Rights and the European Union have played an indispensable role in this transition. However, European institutions' engagement in the Kurdish issue has not always been coherent, while their impact on Turkey's policies has been limited, and at times negative, particularly in the post-9/11 context. Their uncritical oversight has facilitated Turkey's reluctance to undertake structural reforms to bring an end to the selective prosecution of Kurdish politicians, the criminalisation of non-violent advocacy of enhanced rights for the Kurds, the armament of civilians in the Kurdish region and the impunity of state officials who commit human rights violations. Recent developments in Turkey have shown, once again, that a genuine democratic transition will only be possible with the coherent, continuous and critical engagement of European institutions in the Kurdish issue. (SWP Research Paper)
Keywords: 320